Evaluation of long-chain acyl-coenzyme A synthetase 4 (ACSL4) expression in human breast cancer - Negar Dinarvand; Hossein Khanahmad; Sayyed Mohammadreza Hakimian; Abdolkarim Sheikhi; Bahman Rashidi; Morteza Pourfarzam (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: Breast cancer (BC) is one of the major causes of female cancer-related death. It has recently been demonstrated that metabolic reprogramming including alteration in lipid metabolism is indicated in various types of cancer. The enzymes of the acyl-coenzyme A synthetase long-chain family (ACSLs) are responsible for converting fatty acids to their corresponding fatty acyl-coenzyme A esters which are essential for some lipid metabolism pathways. ACSL4 is one of the isoforms of ACSLs and has a marked preference for arachidonic and eicosapentaenoic acids. The objective of this study was to evaluate ACSL4 expression, its prognostic significance, and its correlation with p53 tumor suppressor in BC patients. Experimental approach: In this study 55 pairs of fresh samples of BC and adjacent non-cancerous tissue were used to analyze ACSL4 expression, using real-time polymerase chain reaction and immunohistochemistry (IHC) staining. The expression of other studied variables was also examined using the IHC technique. Findings / Results: ACSL4 expression was significantly higher in BC tissues compared to the adjacent normal tissue. This upregulation was negatively correlated with Ki-67 and age, and positively correlated with p53 status. The correlation between ACSL4 and p53 may indicate the role of p53 in the regulation of lipid metabolism in cancer cells, in addition to its role in the regulation of ferroptosis cell death. Conclusion and implications: Our results indicated that the expression of ACSL4 may be considered as a prognostic indicator and potential therapeutic target in BC. However, further studies are needed to confirm the significance of these findings.